Competitive Strategy Analysis of Production Growth and Consumer Buying Interest in UKM Arumanis in Laren District – Lamongan - Edie Sugiarto (Institute of Computer Science (IOCS), 2020)
Current business developments are demanded in competition in all business fields as well as a dynamic consumer mindset. At this time companies are required to be able to create a product that is able to compete. The purpose of this research was to determine how the influence of competitive strategies and regulatory contexts on buying interest in UKM. By using the Arumanis UKM in Pesanggarahan Village as a sample. This type of research uses quantitative research methods while the analysis used is multiple linear regression. The analysis method used is quantitative method using validity test, reliability test, multiple linear regression assumption, correlation test, determination coefficient, F test, T test. Based on the validity test for the three independent variables (X) and the dependent variable (Y) above obtained rhitung> rtabel (0.300), so that all indicators of the two variables are declared valid. The results of reliability testing with SPSS Alpha Cronbakh's method obtained alpha coefficients on the independent variables. Product variation X1 = 0.928. Rhitung X2 = 0.956, rcount Y = 0.885 greater than the reliability standard (0.600) with a significant level, it can be concluded that the instrument in the independent and dependent variables is reliable. From all the results above, it can be concluded that the Competitive Strategy (X1) has a significant effect on Buying Interest (Y). Regulatory context (X2) has no effect on Buying Interest (Y). Competitive Strategy and Regulatory Context jointly (simultaneously) affect Buying Interest in Arumanis UKM in Pesanggarahan Village. The Competitive Strategy variable (X1) becomes the dominant variable that affects Buying Interest (Y).